Ukraine pharmaceutical sector: current state of legal regulation - O. H. Aleksieiev (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2020)
The purpose of the work. Analysis of the legislative support of the Ukraine pharmaceutical sector, the study of problematic issues of the legal protection of sectoral legal relations in order to formulate proposals for improving the legal protection of the rights of subjects of the Federal Security Service of Ukraine.